The Influence of Institutional Ownership and Company Size on Capital Structure in Manufacturing Companies on Bursa Efek Indonesia - Dewi, Nia Kania; Azis, Azolla Degita; Rizqi, Muhammad Nur (LPPM UIKA Bogor, 2024)
This research aims to determine the effect of institutional ownership and company size on capital structure in manufacturing companies listed on the Indonesia Stock Exchange. The research method used in this research is a quantitative approach by selecting research samples using a purposive sampling method and statistical results are processed using SPSS software. The research sample was 24 manufacturing companies listed on the Indonesia Stock Exchange in 2008-2022. The research results show that institutional ownership does not have a positive effect on capital structure. The greater the amount of institutional ownership, the capital structure does not change. The proportion of company share ownership by institutions indicates that there is a monitoring agent from the institution on management performance so that management will be more careful in placing its investment activities and the size of the company does not have an effect on the capital structure, where if the size of the company increases or decreases, the capital structure remains unchanged increase or decrease.